2020
DOI: 10.3390/biom10040649
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Angiotensin Peptides and Peptidomimetics as Angiotensin II Receptor Type 2 (AT2) Receptor Agonists

Abstract: Angiotensin II receptor type 1 and 2 (AT1R and AT2R) are two G-protein coupled receptors that mediate most biological functions of the octapeptide Angiotensin II (Ang II). AT2R is upregulated upon tissue damage and its activation by selective AT2R agonists has become a promising approach in the search for new classes of pharmaceutical agents. We herein analyzed the chemical evolution of AT2R agonists starting from octapeptides, through shorter peptides and peptidomimetics to the first drug-like AT2R-selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 79 publications
(145 reference statements)
0
17
0
Order By: Relevance
“…AT1R is synthesized on the endoplasmic reticulum and transported to Golgi apparatus for post-translational modification, then to Ang II on the cell membrane surface to stimulate signaling pathways. Finally, it binds to Ang II AT1R to degrade lysosomes ( Vasile et al, 2020 ). In this process, vesicles transport neurotransmitters, proteins or other substances to specific cell sites ( Sheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AT1R is synthesized on the endoplasmic reticulum and transported to Golgi apparatus for post-translational modification, then to Ang II on the cell membrane surface to stimulate signaling pathways. Finally, it binds to Ang II AT1R to degrade lysosomes ( Vasile et al, 2020 ). In this process, vesicles transport neurotransmitters, proteins or other substances to specific cell sites ( Sheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rab proteins participate in vesicle transport through exocytosis and endocytosis. Current studies have shown that Rab1 protein can regulate the anterograde transport of AT1R from endoplasmic reticulum, through Golgi apparatus and to cell surface, thus promoting vascular remodeling ( Connor et al, 2015 ; Raza et al, 2018 ; Vasile et al, 2020 ). Therefore, we primarily proved that AT1R vesicle transport might be mediated by Rab1 in vascular remodeling in DMCI ( Schöppner et al, 2016 ; Yang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective analysis in the chemical evolution of AT2R peptide agonists by molecular binding modes and affinity estimations with the free energy perturbation method has shown that CG42112A presents a guanidine group on a branched-like structure mimicking the side-chain of Arg 2 in Ang II, which explains its strong affinity to AT2R (Vasile et al, 2020).…”
Section: Cgp42112amentioning
confidence: 99%
“…The Ang II induces its pathological vasoconstrictive, proinflammatory and pro-fibrotic effects via G-protein factors such as the angiotensin II type 1 receptors (AT1R) and angiotensin II type 2 receptors (AT2R) [7]. Previous studies conducted in vitro and in vivo have revealed that vascular overload results in an increased release of Ang II followed by activation of AT1R which induces apoptosis in cardiac cells exposed to increased vascular volumes while the ATR2 is also over expressed after myocardial ischemia [8,9,10].…”
Section: The Renin-angiotensin System (Ras)mentioning
confidence: 99%